Trends on epidemiological, virological, and clinical features among newly diagnosed HIV‐1 persons in Northwest Spain over the last 10 years. Issue 8 (16th March 2015) - Pernas, B.; Mena, A.; Cañizares, A.; Grandal, M.; Castro‐Iglesias, A.; Pértega, S.; Pedreira, J.D.; Poveda, E.
<x xml:space="preserve">Abstract</x> To describe temporal trend and characteristics of newly HIV‐diagnosed patients in a medical care area in Northwest Spain over the last 10 years. All newly diagnosed patients for HIV‐infection from 2004 to 2013 at a reference medical care area in Northwest of Spain were identified. Epidemiological, virological, immunological, and clinical data, as well as HIV genotype and drug resistance information were recorded. A total of 565 newly HIV‐diagnosed patients were identified. The number of new cases increased in the last 5 years (66 cases/year). Overall, 53.1% had a median CD4 counts < 350 cells/µl and 33.6% had an AIDS defining criteria. Non‐B variants were found in 34.4% of patients being subtype F (25.8%) the most common non‐B subtype. The rate of transmitted drug resistance (TDR) over the study period was 3.7%, but a decreased to 2.6% was observed in the last 5 years. The most prevalent TDR mutations were: T215 revertants (1.5%), K219QENR (1.2%), for NRTIs; K103N (1.9%), for NNRTIs; L90M (0.3%), for PIs. Overall, 73.2% of patients started antiretroviral treatment and 9.9% of patients died during follow‐up. The number of newly HIV diagnosed patients increased since year 2009. There is a high prevalence of late diagnosis (53%) and 33% had an AIDS defining criteria. Interestingly, the most prevalent non‐B subtype in our population was F (25.8%). These findings support the need to facilitate the access for HIV testing to reduce the rate of late HIV diagnosis, improve the clinical outcome and prevent HIV transmission. J. Med. Virol. 87:1319–1326, 2015. © 2015 Wiley Periodicals, Inc.